Determination of optimal conditions for obtaining phosphate fertilizer from cuban phosphoric rock (2017)
(Eng) In order to reach food security in the country, it is necessary to intensify the production of fertilizers in a sustainable manner in order to obtain increases in productivity, generate economic profits, and increase the use of national raw materials to reduce imports. For these reasons it is necessary to determine the optimum conditions for the process of obtaining Single Superphosphate (SFS), from the phosphate rock and sulfuric acid at lab scale, and thus determine the values ​​of the variables which intervene in that process and assure the maximum quality of the product. To carry out the research, the rotational centered factorial design 22 with star points was used in 13 experimental runs and an experiment matrix was elaborated with the independent variables, acid / rock ratio and percentage of sulfuric acid, in the range of 1.61-2.06 and 65% -75% respectively. As a result it was obtained that the optimum parameters in the range studied for the benefited Cuban rock are: H2SO4 concentration of 72% and acid / rock ratio of 2.02. The quality indexes of the Superphosphate Simple cured obtained with the optimum parameters are: assimilable phosphorus content of 12.28%, humidity 8.21% and free acidity 2.05%; acting in accordance with international product specifications.